2018
DOI: 10.1002/cbic.201800128
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Biosynthesis of Sesquiterpenes Starting from Acetic Acid

Abstract: The enzymatic synthesis of terpenes was investigated by using a cascade based on the mevalonic acid pathway. Suitable enzymes from all kingdoms of life were identified and combined to give rise to geosmin and patchoulol as representative compounds. The pathway was studied in three separate segments, which were subsequently combined in a ten-step cascade plus added cofactor regeneration systems. The cascade delivers farnesyl pyrophosphate with >40 % conversion and cyclises it to sesquiterpenes with >90 % conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…In contrast, it was observed for a carbohydrate precursor synthesis using a four-enzyme cascade that a reduction of reaction temperature from 30 • C to 20 • C led to an increase in yield from 87% to above 95% [37]. The production of sesquiterpenes by Dirkmann et al is another example for the importance of the reaction temperature since they found 30 • C to be the optimal reaction temperature [47]. Temperatures below reduced the conversion and above led to protein precipitation.…”
Section: Reaction Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it was observed for a carbohydrate precursor synthesis using a four-enzyme cascade that a reduction of reaction temperature from 30 • C to 20 • C led to an increase in yield from 87% to above 95% [37]. The production of sesquiterpenes by Dirkmann et al is another example for the importance of the reaction temperature since they found 30 • C to be the optimal reaction temperature [47]. Temperatures below reduced the conversion and above led to protein precipitation.…”
Section: Reaction Temperaturementioning
confidence: 99%
“…Metabolic pathways already existing in organisms can be used as templates and transferred to in vitro multi-enzymatic reactions. These can be parts of the primary metabolism, e.g., glycolysis [46] or of the secondary metabolism such as the mevalonate pathway [47] or chitin degradation [35]. Combinations of primary and secondary pathways were developed to in vitro cascades as well, which produces high value products with the benefit of energy regeneration and the usage of bulk chemicals as substrates.…”
Section: Cascade Design Reaction Pathwaymentioning
confidence: 99%
“…The highest yields with more than 95% and titers of 15 g•L −1 were achieved with a cell-free system consisting of 27 purified enzymes, which convert glucose into monoterpenes [31]. Other systems which incorporate acetic acid as a starting building block for the cell-free synthesis of terpenes are described as well [32]. However, a major drawback is the need for purified enzymes, which are associated with additional costs and the further input of glucose needed to produce them.…”
Section: Progess To An Economic Limonene Production Processmentioning
confidence: 99%
“…However, Schi. pombe has mevalonate pathway to generate terpenes from acetic acid, thereby reducing the stress of acetic acid ultimately in microbiota [43,44]. Therefore, studies need to explore further information about the microbial interactions between S. cerevisiae and non-Saccharomyces yeasts at the molecular level.…”
Section: Discussionmentioning
confidence: 99%